Sophantering från fartyg till hamn till kommun - Sandgren, Michael (My University, 2013)
This paper is a follow up study which was carried out at the Linne University of Kalmar in 2008, which looked at garbage management and its integration between merchant vessels, port reception facilities and the local council. That study was undertaken by Lundgren Lindberg & Roysson. They focused their attention on the integration between vessels calling at the port of Kalmar, the port of Kalmar and Kalmar council. The purpose of this study is to see whether conditions at two other Swedish ports can be compared with the results which were achieved in the study of 2008 and to look at conditions five years on and see if things have improved or if the same problems still remain. It should be note that the international regulations concerning garbage management on board in the case of what and where may be discharged over board vessels have become more stringent with the implementation of the revised version of Marpol annex V, MEPC, 201(62), as well as EMSA (European Maritime Safety Agency) directives on port reception facilities within the EU and which basically follow Marpol. On the other hand regulations concerning garbage management in Swedish ports are still regulated by SJÖFS. 2001:12(Sjöfartsverkets Författningssamling) As with Lundgren Lindberg & Roysson study it has been difficult to find relevant literature on said topic apart from regulatory statutes and recommendations, therefore a qualitative study will be used and for the study so as it can be comparable to the previous one as well as fair. The questions asked will be of the same nature and character as were asked in Lundgren Lindberg & Roysson report and this for the same reasons as mentioned above. The main difference of the new study is that it will look at two ports, two councils and a number of vessels. The results that this study has reached vary from ship to ship, from port to port as well as from municipality to municipality. The one thing that everybody who took part in this study could agree on is that a single standard for the handling of ship generated garbage and its integration from merchant ships to port reception facilities and the local councils is missing. The systems which are in place today work satisfactorily but have certain problems with fractioning the different types of waste and are they sorted incorrectly, problems will arise all the way through the transportation chain. Certain principals have solved these problems by having manned port reception facilities and others have left it up to the crews on board the vessels that they will sort the garbage the way the port wishes it to be sorted. The problems do not seem to take any out of the ordinary proportions if only two ports are considered, but should the merchant fleet worldwide be considered, these proportions would grow alarmingly.
Keywords: Transportteknik och logistik; Transport Systems and Logistics